Analisis Persepsi Masyarakat terhadap Transparansi Pemerintahan Desa Pasca Kasus Suap Rekrutmen di Kecamatan Tulangan - Ita Ayu Wulandari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The alleged bribery case in the recruitment of village officials in Tulangan District, Sidoarjo Regency, has become one of the issues affecting public perceptions of the transparency of village government implementation. This practice is considered contrary to the principles of good governance because it reduces openness, accountability, and public trust in the village government. This study aims to analyze public perceptions of village government transparency following the bribery case in the recruitment of village officials in Tulangan District, identify factors influencing these perceptions, and explain possible measures to strengthen village government transparency. The study used a qualitative approach using a literature review method. Data were obtained from various secondary sources, including scientific journals, books, laws and regulations, official government documents, court decisions, and relevant media coverage. The analysis was conducted through identification, classification, interpretation, and synthesis of various sources related to the research focus. The results of the study indicate that the bribery case has resulted in a decline in public perceptions of information transparency, access to information, accountability, the decision-making process, and trust in the village government. These perceptions are influenced by public service experience, media coverage, apparatus integrity, the effectiveness of village government communication, and community participation. Strengthening transparency through information disclosure, increased accountability, digitalization of services, and public involvement in oversight are crucial steps to restore public trust.